Varieties of Pharmacological Treatment of Bronchial Asthma (Eurasian Medical Research Periodical, 2023)
One of the most common chronic diseases in both adults and children is bronchial asthma (BA). It not only reduces the quality of life of patients, but can also lead to disability [1]. Late diagnosis and inadequate therapy are the main causes of severe course and high mortality from this disease. Modern asthma therapy is aimed at eliminating allergic inflammation of the bronchial mucosa, reducing bronchial hyperreactivity, restoring bronchial patency and eliminating bronchospasm, and preventing structural changes in the bronchial wall